2009
DOI: 10.1111/j.1399-0004.2009.01177.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel and recurrent germline LEMD3 mutations causing Buschke–Ollendorff syndrome and osteopoikilosis but not isolated melorheostosis

Abstract: Mutations in the LEMD3 gene were recently incriminated in Buschke-Ollendorff syndrome (BOS) and osteopoikilosis, with or without melorheostosis. The relationship of this gene with isolated sporadic melorheostosis is less clear. We investigated LEMD3 in a two-generation BOS family showing an extremely variable expression of the disease, in a sporadic patient with skin features of BOS, and in an additional subject with isolated melorheostosis. We identified two different mutations, both resulting in a premature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 32 publications
2
27
0
2
Order By: Relevance
“…Beginning in 2005, (29,30) we verified their finding that germline LEMD3 mutation underlies OPK and BOS, including instances with MEL, but showed that germline LEMD3 mutation does not explain sporadic MEL. (31) Our conclusion was subsequently supported in 2006 by Hellemans et al, (61) and in 2009 by Zang et al, (32) and then by others. (62) In 2010, we reported evidence that rarely BOS could be genetically heterogeneous.…”
Section: V) Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Beginning in 2005, (29,30) we verified their finding that germline LEMD3 mutation underlies OPK and BOS, including instances with MEL, but showed that germline LEMD3 mutation does not explain sporadic MEL. (31) Our conclusion was subsequently supported in 2006 by Hellemans et al, (61) and in 2009 by Zang et al, (32) and then by others. (62) In 2010, we reported evidence that rarely BOS could be genetically heterogeneous.…”
Section: V) Discussionsupporting
confidence: 61%
“…This was confirmed by others. (32) MEL in OPK or BOS had been postulated previously to reflect a somatic “second hit” mutation of some gene, (28,31) subsequently including LEMD3 itself, (33) but sporadic MEL remained unexplained.…”
Section: Ii) Introductionmentioning
confidence: 99%
“…A LEMD3 investigation in a two-generation BOS family showed extreme intrafamilial clinical variability of LEMD3 mutations, which underlines the lack of a clear phenotype–genotype correlation in BOS [12]. Another case describing the absence of LEMD3 mutation in an affected family may indicate the genetic heterogeneity of Buschke–Ollendorff syndrome [13].…”
Section: Discussionmentioning
confidence: 99%
“…BOS is an autosomal dominant disease, described in several series in the literature as recurring in families (Hellemans et al, 2004, Kawamura et al, 2005, Yadegari et al, 2010, Zhang et al, 2009). The causative mutation is believed to be in the gene encoding the LEM domain-containing protein 3 (LEMD3), an inner nuclear membrane protein, which, via interactions through Smad proteins, plays a key role in the regulation of transforming growth factor beta (TGF-β) and bone morphogenic protein (Hellemans et al, 2004, Zhang et al, 2009). Abnormal function of mutant LEMD3 leads to unmitigated TGF-β signaling and consequent increased steady-state levels of elastin messenger RNA (mRNA) and elastin accumulation in the dermis (Woodrow et al, 2001).…”
Section: Buschke-ollendorff Syndromementioning
confidence: 99%